KNOWLEDGE, ATTITUDE, PRACTICE, AND PERCEPTION TOWARDS COVID-19 IN NORTH EASTERN STATES OF INDIA: AN ONLINE CROSS SECTIONAL STUDY - SRIVASTAVA, AMIT; BALA, RENU; SHIL, RATAN CHANDRA; SHAW, PRABIN KUMAR; KARSO, LIYI; BHAUMIK, HIMADRI; TAMANG, SANTOSH KUMAR; BHATTACHARJEE, BAIDURJYA; NATH, TAPAN; CHAKMA, ABHIJIT; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study aimed to assess knowledge, attitude, practices, and perception (KAP) toward COVID-19 among the population of eight North Eastern (NE) states of India. Methods: A cross-sectional study from June 30 to July 13, 2020 was carried out through a self-reported, structured questionnaire that was circulated online to participants of age group of 18 years or above. Convenient sampling was used to recruit respondents for the study. Results: The study received responses from 8309 participants. Key findings revealed that most respondents had good knowledge of preventive measures and common symptoms of COVID-19. The majority of the respondents showed a good attitude and adopted preventive practices. The mean score of knowledge was 7.137, attitude was 16.132, practice was 9.379, and perception was 13.583. The scores of four KAP categories significantly differed across most of the demographic variables (p<0.001). The majority of people took homoeopathic medicine as prophylaxis for immune booster. Conclusion: The study highlights that the focus on behavioral change communication in all the NE states could be strengthened, especially in rural areas. Advocacy based on the comprehensive list of symptoms for COVID-19 may also be bolstered. There is scope for strategically promoting knowledge, immunity boosting, and self-care practices suggested in the AYUSH systems of medicine.